One new species of the subgenus Xizicus (Zangxizicus) (Orthoptera: Tettigoniidae: Meconematinae) from China - Lin, Chang Yan; Xia, Su Cai; Ming, Shi Fu (Zootaxa, 2016)
The paper reports one new species of the tribe Meconematini, Xizicus (Zangxizicus), curvus Chang & Shi sp. nov., and supplies the character photographs of the new species and Xizicus(Zangxizicus) tibeticus Wang, Jing, Liu & Li, 2014.